The QoG Agency Database - Agency Head (1960-2014) - Dahlström, Carl; Holmgren, Mikael; Department of Political Science, University of Gothenburg (University of Gothenburg, 2019)
This database consists of a comprehensive sample of administrative agencies in the Swedish executive bureaucracy between 1960 and 2014. The purpose of the dataset is to provide a quantitative catalogue of Swedish agencies for public use.

Scholars who wish to use this dataset in their research are kindly requested to use the following
citation:
Dahlström, Carl, Mikael Holmgren, Christian Björkdahl, Kersti Hazell, Anna Khomenko, Richard Svensson, and Pär Åberg. 2018. "Swedish Administrative Agencies, 1960-2014." University of Gothenburg: The Quality of Government Institute.

This database consists of a comprehensive sample of administrative agencies in the Swedish executive bureaucracy between 1960 and 2014. The purpose of the dataset is to provide a quantitative catalogue of Swedish agencies for public use.

Scholars who wish to use this dataset in their research are kindly requested to use the following
citation:
Dahlström, Carl, Mikael Holmgren, Christian Björkdahl, Kersti Hazell, Anna Khomenko, Richard Svensson, and Pär Åberg. 2018. "Swedish Administrative Agencies, 1960-2014." University of Gothenburg: The Quality of Government Institute.
The QoG Agency Database - Agency Head (1960-2014)
Keywords: BUREAUCRACY; BYRÅKRATI; agency head; agency head; Sweden; Sverige; agency; agency; public administration; offentlig förvaltning; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Public Administration Studies; Studier av offentlig förvaltning